FORMATION OF TOILET HABITS IN CHILDREN IN MOSCOW. RETROSPECTIVE STUDY RESULTS. PART II - G. A. Karkashadze; L. S. Namazova-Baranova; O. I. Maslova; A. K. Gevorkyan; S. B. Lazurenko; S. N. Zorkin; E. V. Komarova; A. K. Gevorkyan; O. I. Denisova; S. D. Polyakov; T. A. Konstantinidi (Педиатрическая фармакология)
The results of the first Russian study of toilet habits formation in children have been obtained. The article was planned to be published in 2 subsequent parts due to the extensiveness of the material. This article is the 2nd part*. It presents and comments on the remaining part of results in the form of the connection between main parameters and characteristics of toilet habits training processes and physiological, psychological and social factors; it also presents the discussion and conclusions. Comparative data (with foreign studies) is given. A multitude of both physiological and social factors affect the process of children’s toilet habits training. The following physiological factors have been revealed: stool frequency, physiological involuntary night urination, peculiarities of falling asleep and pernicious habits – processes, which reflect the intestinal motility regulation and defecation states, urination control and neuropsychic activity. The selected training strategy and tactics, style of communication with a child also affect the training process. The most influential family-social factors in terms of toilet habits training processes are: two- or one-parent family, mother’s education and twins in the family.